From Data Ambiguity to Legitimate Decisions: Sensemaking and Communicative Leadership in Rural Data Governance under VUCA Conditions - Veranus Sidharta; Sarwititi Sarwoprasodjo; Henny Warsilah; Eko Wahyono (Universitas Muhammadiyah Tangerang, 2026)
This study examines how village governments navigate data governance in a VUCA context, where a gap exists between administrative data and socially constructed, inclusive realities in targeting social assistance. Using a qualitative comparative case study, this study analyzes two village contexts: Karangtengah and Rawapanjang, with interviews involving village heads and neighborhood (RT) leaders. The findings suggest that effective data governance under VUCA is determined not only by data quality but also by the integration of three mechanisms: understanding, communicative leadership, and inclusive verification. This study reconceptualizes data governance as a socio-interpretive and communicative process and proposes an adaptive governance framework that explains how ambiguity translates into legitimate decisions. These findings highlight the importance of integrating local verification mechanisms into broader policy design to improve targeting accuracy, inclusion, and policy legitimacy.Studi ini meneliti bagaimana pemerintah desa menavigasi tata kelola data dalam konteks VUCA, di mana terdapat kesenjangan antara data administratif dan realitas inklusif yang dibangun secara sosial dalam menargetkan bantuan sosial. Menggunakan studi kasus komparatif kualitatif, studi ini menganalisis dua konteks desa: Karangtengah dan Rawapanjang, dengan wawancara yang melibatkan kepala desa dan pemimpin lingkungan (RT). Temuan menunjukkan bahwa tata kelola data yang efektif di bawah VUCA ditentukan tidak hanya oleh kualitas data tetapi juga oleh integrasi tiga mekanisme: pemahaman, kepemimpinan komunikatif, dan verifikasi inklusif. Studi ini merekonseptualisasi tata kelola data sebagai proses sosio-interpretatif dan komunikatif serta mengusulkan kerangka kerja tata kelola adaptif yang menjelaskan bagaimana ambiguitas diterjemahkan menjadi keputusan yang sah. Temuan ini menyoroti pentingnya mengintegrasikan mekanisme verifikasi lokal ke dalam desain kebijakan yang lebih luas untuk meningkatkan akurasi penargetan, inklusi, dan legitimasi kebijakan.